Chemical profiling of Sanjin tablets and exploration of their effective substances and mechanism in the treatment of urinary tract infections - Li, Meng-Yuan; Li, Yang; Wang, Li-Li; Xu, Feng; Guo, Xu-Yan; Zhang, Jing; Lv, Yang; Wang, Peng-Pu; Wang, Shun-Qi; Min, Jian-Guo; Zou, Xun; Cai, Shao-Qing (Frontiers in Chemistry, 2023)
Sanjin tablets (SJT) are a well-known Chinese patented drug that have been used to treat urinary tract infections (UTIs) for the last 40 years. The drug consists of five herbs, but only 32 compounds have been identified, which hinders the clarification of its effective substances and mechanism. Therefore, the chemical constituents of SJT and their effective substances and functional mechanism involved in the treatment of UTIs were investigated by using High performance liquid chromatography-electrospray ionizationion traptime of flight- mass spectrometry (HPLC-ESI-IT-TOF-MSn), network pharmacology, and molecular docking. A total of 196 compounds of SJT (SJT-MS) were identified, and 44 of them were unequivocally identified by comparison with the reference compounds. Among 196 compounds, 13 were potential new compounds and 183 were known compounds. Among the 183 known compounds, 169 were newly discovered constituents of SJT, and 93 compounds were not reported in the five constituent herbs. Through the network pharmacology method, 119 targets related to UTIs of 183 known compounds were predicted, and 20 core targets were screened out. Based on the “compound–target” relationship analysis, 94 compounds were found to act on the 20 core targets and were therefore regarded as potential effective compounds. According to the literature, 27 of the 183 known compounds were found to possess antimicrobial and anti-inflammatory activities and were verified as effective substances, of which 20 were first discovered in SJT. Twelve of the 27 effective substances overlapped with the 94 potential effective compounds and were determined as key effective substances of SJT. The molecular docking results showed that the 12 key effective substances and 10 selected targets of the core targets have good affinity for each other. These results provide a solid foundation for understanding the effective substances and mechanism of SJT.